Three-component spectroelectrochemical sensor module for the detection of pertechnetate (TcO4-) - Chatterjee Sayandev; Bryan Samuel A.; Seliskar Carl J.; Heineman William R. (Reviews in Analytical Chemistry, 2013)
This review looks at the advancements in the development of a sensor for technetium (Tc) that is applicable to characterizing and monitoring the vadose zone and associated subsurface water. Subsurface contamination by Tc is of particular concern for two reasons: the long lifetime of its most common isotope 99Tc (half-life=2×105 years) and the fast migration in soils of pertechnetate (TcO4-), which is considered to be the dominant 99Tc species in ground water. TcO4– does not have a characteristic spectral signature which prevents its rapid, sensitive, and economic in situ detection. To address this problem, a novel spectroelectrochemical sensor has been designed, that combines three modes of selectivity (electrochemistry, spectroscopy, and selective partitioning) into a single sensor to substantially improve specificity, which is critical in the specific detection of an analyte in the presence of potential interfering species. The sensor consists of a basic spectroelectrochemical configuration: a waveguide with an optically transparent electrode (OTE) that is coated with a thin chemically-selective film that preconcentrates the analyte. The key to adapting this generic sensor to detect TcO4- and Tc complexes lies in the development of chemically-selective films that preconcentrate the analyte and, when necessary, chemically convert it into a complex with electrochemical and spectroscopic properties appropriate for sensing. The chemically selective films can be combined with ligands which are capable of reacting with TcO4- to form coordination complexes, the spectral properties of which can be used to enhance the sensitivity of detection. The first half of this review describes the general concept of the sensor and the rationale for the selection of its specific components, and the development and characterization of the sensor for the different detection modules. The second half summarizes the synthesis and characterization of complexes relevant for the detection of technetium, and the progress in the utilization of the sensor module for the effective detection of these complexes.